Development of Sentiment of Sweetness in Hindi Literature : हिन्दी साहित्य में माधुर्यभाव का विकास - Singh, Vikram (RESEARCH HUB International Multidisciplinary Research Journal, 2024)
In the world, the union of man and woman holds significant importance. In every particle of creation, there exists an intense desire for mutual attraction inspired by passion, and an ardent aspiration for union. In the history of Indian literature, the instinct of passion has been given importance since ancient times. Tulsidas, in his work Ramcharitmanas, has vividly depicted this concept. According to him, the desire for union resides eternally in everyone’s heart. Vatsyayana, the philosophical analyst of the theory of passion, also considered passion as the most universal, innate impulse that drives all actions of living beings and the essence of life. While explaining passion, he stated that passion is love, it is joy, and it is the attainment and satisfaction of conjugal bliss. The word madhurya (sweetness) is polysemous. Generally, it implies sweetness, but beyond that, it also signifies beauty, charm, love, attraction, and more. Abstract in Hindi Language: संसार में नर-नारी के संयोग का महत्वपूर्ण स्थान है। सृष्टि के कण-कण में पारस्परिक काम प्रेरित आकर्षण पारस्परिक मिलन की उत्कट आकांक्षा तीव्रतम रूप में विद्यमान है। भारतीय साहित्य इतिहास में काम प्रवृति को प्राचीन काल से ही महत्व दिया जा रहा है। तुलसीदास जी ने भी अपनी रचना रामचरितमानस में सजीव चित्रण किया है उनकी दृष्टि में भी सबके हृदय में मदन की अभिलासा संयोगेच्छा शाष्वत है। काम सिद्धांत के तात्विक विवेचक वात्सायन ने भी काम को सर्वाधिक व्यापक, प्राणीमात्र के समस्त कार्यकलाप का उत्प्रेरक, जीवन का जन्मजात मौलिक भाव माना है। काम की व्याख्या करते हुए उन्होंने बतलाया है कि काम ही प्रेम है, काम ही सुख है और काम ही दाम्पत्य आनंद की प्राप्ति एवं संतुष्टि है। मार्धुय शब्द अनेकार्थी है। सामान्य अर्थों में इस शब्द से मधुरता का तात्पर्य है किंतु मधुरता के अतिरिक्त इस शब्द का व्यवहार सुंदरता मिठास, प्रेम, आकर्षण आदि अर्थों में भी किया गया है। Keywords: संसार, तुलसीदास, रामचरितमानस, वात्सायन व्यापक हृदय, उत्प्रेरक, दाम्पतय, सुन्दरता, आकर्षण